Performance Assessment of a Counter Flow Cooling Tower – Unique Approach. (March 2017) - Naik, B. Kiran; Choudhary, V.; Muthukumar, P.; Somayaji, C.
Abstract: Cooling tower is one of the most suitable system for evaporative cooling of hot water in comparison with other types of evaporative cooling systems. In the present study, a finite difference model is developed for predicting the characteristics of coupled heat and mass transfer processes occurring in a counter flow forced draft cooling tower. This model consists of thermal effectiveness, height of the tower and moisture effectiveness as variable parameters, and provides a correlation for heat and mass transfer coefficients in order to obtain the desired performance parameters. The predicted results for evaporative cooling process are in good agreement with the experimentally measured data. The mathematical model developed in this study can be used as a tool for predicting the cooling tower performance characteristics.